Tahlil ¸Thuruq Istinbat Ahkam al-ÄyÄt allatI Ya'tariha al-Iná¸hiraf al-Balaghi fi Kitab Ah¸kam al-Qur'ân lil-Jassás - Wahyuddin; M. Kamil Ramma Oensyar (Jurnal Al-Maqoyis, 2025)
This study examines rhetorical deviations in the Qurâ€™an, focusing on verses that are syntactically declarative but convey injunctive meaning, and vice versa. It explores how this phenomenon affects the derivation of legal rulings in Al-Jaá¹£á¹£Äsâ€™ Aá¸¥kÄm al-Qurâ€™Än. Using qualitative textual analysis, the study combines linguistic and exegetical approaches, supplemented with comparisons to Prophetic traditions (á¸¥adÄ«th) and scholarly opinions to support jurisprudential interpretations. The findings reveal that shifts between declarative and injunctive styles serve to emphasize deeper legal meanings. For example, Surah Al-Baqarah 2:233, although declarative, â€œAnd the mothers shall breastfeeâ€, functions as a command regarding the nursing duration. Similarly, Surah An-Nur 24, while declarative in form, affirms specific obligations or prohibitions. Conversely, injunctive verses may carry declarative meaning, as in Surah At-Tawbah 9:5, clarifying the non-acceptance of hypocritesâ€™ deeds, or Surah Al-Baqarah 2:125, where the directive to use the station of Abraham (maqÄm IbrÄhÄ«m) underscores ritual significance. Overall, the interplay between declarative and injunctive styles reinforces the clarity of Islamic legal rulings, as exemplified in Surah Al-Aâ€˜rÄf 7:29, where a declarative context transitions into an injunctive command to uphold justice and perform prayer.